Digitalization and Performance of Dompet Dhuafa’s Qurban Program - Muhammad Farid, Nano; Jamal Abdul Aziz (Islamic Economics and finance in Focus, 2026)
Digital Islamic philanthropy should be assessed not only by transaction convenience, but also by allocation efficiency and the expansion of social benefits. This study evaluates the performance of Dompet Dhuafa's Tebar Hewan Kurban program using a quantitative, non-experimental secondary-data design. The data comprise audited financial statements for 2023-2024 and official program outcomes for 2023, 2025, and 2026. The analysis applies allocation ratios, growth rates, compound annual growth rates (CAGR), and outreach productivity. Qurban-fund income increased by 1.84% in 2024, while the distribution share rose from 84.45% to 85.36%. The support-cost ratio declined from 8.23% to 7.31%. Sheep/goat-equivalent animals increased from 27,419 in 2023 to 40,204 in 2026, with a CAGR of 13.61%; beneficiaries increased from 1,777,080 to 2,504,478, with a CAGR of 12.12%. Outreach productivity recovered from 55.47 to 62.29 beneficiaries per animal equivalent in 2025-2026. The findings associate digital development with greater scale, efficiency, and social reach. However, inconsistencies across publications highlight the need for standardized, auditable, and maqasid-oriented reporting.